Biocontrol potential and underlying mechanism of Trichoderma asperellum C15 against postharvest anthracnose of chili pepper - Jie Zhong; Rui Guo; Jia Rui Yang; Jin Chen; Xiao Gang Li; Jun Zi Zhu (Postharvest Biology and Technology, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Astronomically forced climate change during the Middle Oligocene-Early Miocene in the Pearl River Mouth Basin, Northern South China Sea - Shizhen Jia; Yanzhen Li; Mengqing Shang; Rui Liu; Linzhen Hu; Yongming Zhang; Xiuju Xing; Zi’ang Yang (Marine Geophysical Research, 2026)

Hydrogel-encapsulated microalgae-bacteria consortia for resilient saline agriculture - Xiao-Jing Wang; Nan Wu; Xiao Yu; Si-Ming Li; Zi-Rui Yang; Zhi-Hai Zhong; Kang Wang; Hong-Li Cui; Cheng-Gang Ren; Song Qin (World Journal of Microbiology and Biotechnology, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Quantifying land-use-specific non-point source pollution in a forest-dominated watershed using control-section mass balance and ridge regression - Zhang Jing; Zhao Rui-rui; Yang Lu Ping; Chen Zi Jing; Xing Bing; Peng Shi-tao (Process Safety and Environmental Protection, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Prevalence and Molecular Characterization of Entamoeba spp. in Pigs in Shanxi Province, North China - Ze-Dong Zhang; Han-Dan Xiao; Dong-Yang Wang; Zi-Rui Wang; Xun-Zhi Liu; Nan Su; Xing-Quan Zhu; Qing Liu; Wen-Wei Gao (Acta Parasitologica, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Spatial Distribution Characteristics of Secondary PM2.5 in Beijing-Tianjin-Hebei Region Based on Time Series Decomposition - Qing Yao; Jing Ding; Zi-rui Liu; Xu Yang; Ying-xiao Tang; Zi-yin Cai; Su-qin Han (Aerosol Science and Engineering, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Effects of mung bean addition on quality and starch anti-digestion mechanism of oat noodles - Rui-xian Shang; Wei-feng Zhang; Zi-hao Tu; Xiu-juan Ren; Yan-xia An; Gui-Hong Yin; Jian Zhang; Yang Zhao (Journal of Cereal Science, 2026)

Infrared spectroscopy combined with deep learning to describe the textural properties of cooked rice from raw materials: revealing spectral variations and internal correlations during processing - Rui Tang; Ting Yu; Zi Li; Junru Wu; Xiaoming Zheng; Leiqing Pan; Yang Chen; Kun Duan; Hui Dong; Weijie Lan (Food Control, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Reducing grain arsenic and extracting soil arsenic in paddies by an integrated ridge–furrow and ferrihydrite–PVA membrane system - Jing-Min Yang; Qiao-Rui Ren; Zi-Xin Liu; Xin Wang; Dong-Xing Guan; Ya-Nan Dai; He Pei; Bo Peng; Qin-Bo Qin (Journal of Environmental Sciences, 2026)

Interfacial charge transfer bridge enables high-quality heterojunction for braided coaxial ammonium-ion asymmetric supercapacitors - Jing Xu; Sheng-Jie Wang; Mao-Lan Liao; Zi-Tao Yang; Jia-Peng Hu; Rui-Lai Liu; Jia-Huan Tang; Zhi-Feng Zheng; Yi-Bing Xie (Chemical Engineering Journal, 2026)

Precise construction of Anderson-type polyoxometalate-based covalent organic frameworks for photocatalytic hydrogen peroxide production - Zhang-Di Liu; Zai-Xiang Zhang; Yang Yang; Rui Xing; Zi-Hao Wei; Hou-He Liu; Jiang-Bo Ming; Jin Zhu; De-Yin Wang (Journal of Water Process Engineering, 2025)

Recent advances and perspectives in coordination polymer-based fluorescent sensors for vitamin detection - Zi-Hao Zhao; Zhi-Wei Liu; Xin-Rui Xu; Qian-Yu Yang; Zhao-Yang Tong (Chemical Engineering Journal, 2025)

Bioactive sulfur-containing amides from the leaves of Glycosmis lucida - Shou-Yuan Wu; Hong-Yan Yang; Zhong-Liu Zhou; Zi-Feng Liang; Rui-Hong Zhu; Jing-Ling Ren; Pei-Lian Liu; Zi-Ming Chen (Natural Product Research, 2025)

Transcriptomic analysis of the mechanism of male reproductive injuries caused by the mixture of three phthalates in rats - Ling-Zi Xia; Jun-Zhe Yue; Li-Jun Wu; Qian-Ying Jin; Yi-Pei Yang; Jing-Yang Yu; Rui-Zhe Pan; Xin Zhang; Xiao-Ying Wu; Jiayin Zhu; Hai-Tao Gao (Toxicology and Applied Pharmacology, 2025)

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Desulfosporosinus sediminicola sp. nov., an acidophilic sulfate-reducing bacterium isolated from acidic sediments of a disused iron mine site - Sheng-Fang Jiang; Chu-Yi Zhang; Xuan-Wen Lao; Wei-Chao Jia; Tao-Tao Yang; Si-Yu Zhang; Ying-Ying Xie; Pei-Zhe Ye; Rui Lan; Zi-Xiang Lai; Qiang Yang; Li-Nan Huang (Antonie van Leeuwenhoek, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Responses of an invasive plant Alternanthera philoxeroides to cadmium, nutrient availability and water temperature - Zi-Yang Xie; Zhi-Hang Liu; Xin-Yue Gu; Yuan-Yuan Qin; Yu-Ting Du; Jin Yan; Rui Zhang; Chao Si (Aquatic Botany, 2025)

Nanoplastics and microplastics released from an enzyme-embedded biodegradable polyester during hydrolysis - Ling Ma; Zi-Yang Fan; Wen-Qian Lian; Xin-Feng Wei; Rui-Ying Bao; Wei Yang (Journal of Hazardous Materials, 2025)

The mouse resource at National Resource Center for Mutant Mice of China - Bingzhou Han; Dongshen Chen; Zhong Chen; Ting Wang; Kaiyuan Zi; Rui Feng; Xiaoliu Yang; Ling’en Li; Juan Liang; Xiang Gao (Mammalian Genome, 2025)

Effects of earthworms on the performance of Lolium multiflorum, soil properties and microbial communities in its root-zone soil under cadmium stress - Xiao-Gai Wang; Bing-Nan Zhao; Zi-Yang Xie; Zhi-Huan Chen; Zhi-Hang Liu; Xiao Chen; Bo-Yang Lu; Jia-Ning Liu; Rui Zhang; Chao Si (Plant and Soil, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

The impact of urban morphology on land surface temperature under seasonal and diurnal variations: Marginal and interaction effects - Zi Wang; Rui Zhou; Yang Yu (Building and Environment, 2025)

How does shared mobility impact metro-based urban commercial travel accessibility and Equity? - Rui Zhou; Yang Yu; Zi Wang; Luheng Ke; Jin Zhao (Transportation Research Part D: Transport and Environment, 2025)

Revealing the impact of urban spatial morphology on land surface temperature in plain and plateau cities using explainable machine learning - Zi Wang; Rui Zhou; Jin Rui; Yang Yu (Sustainable Cities and Society, 2025)

TDCPP promotes apoptosis and inhibits the calcium signaling pathway in human neural stem cells - Ming-Rui Li; Guo-Rui Zhou; Zi-Ye Wang; Bo-Yang Li; Shu-Hui Men; Zhen-Guang Yan (Science of The Total Environment, 2025)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Crystal and micro-nano structure bidirectional regulation of iron oxalate for high-lithium storage and ultralong-cycling life via ultrasound assistance - Qing Zhao; Keyu Zhang; Geng Gao; Bo Jin; Guangping Zi; Rui Yan; Binbin Li; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

Covalent organic framework with bioinspired N,S-anchored single atom sites for photocatalytic CO2 reduction reaction - Zi-Xian Pan; Shuai Yang; Xi Chen; Jing-Xian Luo; Rui-Zhi Zhang; Peng Yang; Qing Xu; Jie-Yu Yue (Chemical Engineering Journal, 2024)

Finite element modeling and analysis of effect of preexisting cervical degenerative disease on the spinal cord during flexion and extension - Meng-lei Xu; Yi-ting Yang; Hui-zi Zeng; Yu-ting Cao; Liang-dong Zheng; Chen Jin; Shi-jie Zhu; Rui Zhu (Medical & Biological Engineering & Computing, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

The Role of Cystathionine-β-Synthase, H2S, and miRNA-377 in Hypoxic-Ischemic Encephalopathy: Insights from Human and Animal Studies - Chun-Yang Liu; Hisham Al-Ward; Ning Liu; Francine Ngaffo Mekontso; Wei Chen; Wenxia Gao; Chunxue Zhang; Abduh Murshed; Zi-Rui Yu; Orion Fan; Yi Eve Sun; Hui Xu (Journal of Molecular Neuroscience, 2023)

Triterpenoid saponins from Psammosilene tunicoides and their antinociceptive activities - Yan-Hong Li; Xi-Shan Bai; Xiu-Xia Yang; Yu-Xiao Li; Hong-Rui Li; Zi-Liang Wang; Wei Wang; Kai Tian; Xiang-Zhong Huang (Phytochemistry, 2023)

A coumarin-based multifunctional chemosensor for Cu2+/Al3+ as an AD theranostic agent: Synthesis, X-ray single crystal analysis and activity study - Xiaodi Kou; Chengting Hu; Zi Pang; Xinyu Zhang; Huiyan Wang; Rui Shen; Aihong Yang (Analytica Chimica Acta, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Numeric and nonnumeric information input to predict adsorption amount, capacity and kinetics of tetracyclines by biochar via machine learning - Bai-Qin Zhou; Rui-Chun Yang; Hui-Ping LI; Yu-Jun Wang; Chun-Yue Zhang; Zi-Jie Xiao; Zhong-Qi He; Wei-Hai Pang (Chemical Engineering Journal, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

A semi-analytical method for predicting train-induced vibrations considering train-track-soil and soil-pile-building dynamic interactions - Zi-Yu Tao; Chao Zou; Guang-Rui Yang; Yi-Min Wang (Soil Dynamics and Earthquake Engineering, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Target acquisition of anti-aging manno-oligosaccharide that triggers ECM process via TGF-β/Smads-SIRT1 signalling pathway - Liu Yang; Chengting Zi; Dingkang Chen; Jinyu Li; Rui He; Jiang-Miao Hu (Carbohydrate Polymers, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Naïve-like conversion of bovine induced pluripotent stem cells from Sertoli cells - Yu Jiang; Ning-Ning Cai; Xing-Lan An; Wen-Qian Zhu; Rui Yang; Bo Tang; Zi-Yi Li; Xue-Ming Zhang (Theriogenology, 2023)

Surrogacy of bird species in systematic conservation planning and conservation assessments in Yunnan Province, China - Jian Zhou; Fei-ling Yang; Zi-jie Zhong; Ji Zhang; Xian Leng; Jin Ye; Rui-dong Wu (Journal of Mountain Science, 2022)

Gastrodin Regulates the Notch Signaling Pathway and Sirt3 in Activated Microglia in Cerebral Hypoxic-Ischemia Neonatal Rats and in Activated BV-2 Microglia - Jing Guo; Xiao-Li-Na Zhang; Zhang-Rui Bao; Xue-Ke Yang; Ling-Shuang Li; Yu Zi; Fan Li; Chun-Yun Wu; Juan-Juan Li; Yun Yuan (NeuroMolecular Medicine, 2021)

Optimizing staggered-grid finite-difference method based on the least-squares combination of the square window function - Chao-pu Chen; Hong Liu; Zhi-yang Wang; Wen-lei Bai; Cheng-fang Zhang; Zi-rui Meng (Applied Geophysics, 2021)

Benefit–risk assessment of commonly consumed fish species from South China Sea based on methyl mercury and DHA - Ping Wang; Shao-wei Chen; Zi-hui Chen; Wei-lun Huo; Rui Huang; Wei-xiong Huang; Jie-wen Peng; Xing-fen Yang (Environmental Geochemistry and Health, 2019)

Relationship between stand characteristics and soil properties of two typical forest plantations in the mountainous area of Western Sichuan, China - Hao Yang; Ning Miao; Shao-cai Li; Rui Ma; Zi-yan Liao; Wei-ping Wang; Hai-long Sun (Journal of Mountain Science, 2019)

Health Risk Assessment for Local Residents from the South China Sea Based on Mercury Concentrations in Marine Fish - Shao-wei Chen; Zi-hui Chen; Ping Wang; Rui Huang; Wei-lun Huo; Wei-xiong Huang; Xing-fen Yang; Jie-wen Peng (Bulletin of Environmental Contamination and Toxicology, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Tbx18-dependent differentiation of brown adipose tissue-derived stem cells toward cardiac pacemaker cells - Lei Chen; Zi-Jun Deng; Jian-Sheng Zhou; Rui-Juan Ji; Xi Zhang; Chuan-Sen Zhang; Yu-Quan Li; Xiang-Qun Yang (Molecular and Cellular Biochemistry, 2017)

Synthesis and evaluation of multifunctional ferulic and caffeic acid dimers for Alzheimer’s disease - Xi-xin He; Xiao-hong Yang; Rui-ying Ou; Ying Ouyang; Sheng-nan Wang; Zi-wei Chen; Shi-jun Wen; Rong-biao Pi (Natural Product Research, 2017)

A new flavane acid from the fruits of Illicium verum - Liang-Deng Wu; Chun-Lan Xiong; Zi-Zhan Chen; Rui-Jie He; Yan-Jun Zhang; Yan Huang; Sheng-Ping Deng; Rui-Yun Yang; Jun Li (Natural Product Research, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

A new bibenzyl derivative with nuclear factor-kappaB inhibitory activity from Schefflera arboricola (Araliaceae) - Hang Li; Zi-Zhe Cai; Long-Ping Zhu; Xin-Jun Xu; Shao-Rui Chen; De-Po Yang; Zhi-Min Zhao (Natural Product Research, 2015)

The association between the Lys751Gln polymorphism in the XPD gene and the risk of bladder cancer - Tianyuan Xiong; Jiqiao Yang; Haichuan Wang; Fanyi Wu; Yang Liu; Rui Xu; Zi Lv; Pei Xue; Wen Cao; Yonggang Zhang (Molecular Biology Reports, 2014)

Cloning of three members of acc synthase gene family in sugarcane - Ai-Qin Wang; Li-Tao Yang; Zi-Zhang Wang; Yu-Tuo Wei; Long-Fei He; Yang-Rui Li (Sugar Tech, 2006)

Trehalose synthase gene transfer mediated byAgrobacterium tumefaciens enhances resistance to osmotic stress in sugarcane - Zi-Zhang Wang; Shu-Zhen Zhang; Ben-Peng Yang; Yang-Rui Li (Sugar Tech, 2005)